Pengaruh Rasio Likuiditas, Financial Leverage, Operating Capacity, dan Sales Growth Terhadap Financial Distress (Studi Empiris Perusahaan Farmasi Yang Terdaftar di BEI - Ilham Febriansyah; Budi Wahono; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Every company was founded with the aim of obtaining the greatest profit. But along the way, each company will be different. There will be a phase of increasing or decreasing the company's financial condition. As a result, it is necessary to predict the possibility of financial distress in the company using the analysis of this research. This analysis will greatly affect the company in taking future steps. This study was conducted to knowing the effect of liquidity ratios, financial leverage, operating capacity, and sales growth on financial distress. This analysis looked at pharmaceutical companies that were on the IDX from 2016 to 2019. This research using purposive sampling method as the sampling technique with a sample of nine companies. Data were taken from the IDX website using documentation techniques. Data were analyzed by using multiple linear regression. The results of the analysis of this study state that the ratio of liquidity, financial leverage, and operating capacity affects financial distress, while sales growth does not affect financial distress. Keywords : Liquidity Ratio, Financial Leverage, Operating Capacity, Sales Growth, Financial Distress